Bedaquiline, Delamanid, Linezolid, and Clofazimine for Treatment of Pre-extensively Drug-Resistant Tuberculosis. (29th June 2022) - Padmapriyadarsini, Chandrasekaran; Vohra, Vikram; Bhatnagar, Anuj; Solanki, Rajesh; Sridhar, Rathinam; Anande, Lalitkumar; Muthuvijaylakshmi, M; Rana, Meera Bhatia; Jeyadeepa, Bharathi; Taneja, Gaurav; Balaji, S; Shah, Prashant; et al.
Abstract: Background: Treatment success rates for multidrug-resistant tuberculosis (MDR-TB) remain low globally. Availability of newer drugs has given scope to develop regimens that can be patient-friendly, less toxic, with improved outcomes. We proposed to determine the effectiveness of an entirely oral, short-course regimen with bedaquiline and delamanid in treating MDR-TB with additional resistance to fluoroquinolones (MDR-TBFQ+ ) or second-line injectable (MDR-TBSLI+ ). Methods: We prospectively determined the effectiveness and safety of combining 2 new drugs with 2 repurposed drugs—bedaquiline, delamanid, linezolid, and clofazimine—for 24–36 weeks in adults with pulmonary MDR-TBFQ+ and/or MDR-TBSLI+ . The primary outcome was a favorable response at end of treatment, defined as 2 consecutive negative cultures taken 4 weeks apart. The unfavorable outcomes included bacteriologic or clinical failure during the treatment period. Results: Of the 165 participants enrolled, 158 had MDR-TBFQ+ . At the end of treatment, after excluding 12 patients due to baseline drug susceptibility and culture negatives, 139 of 153 patients (91%) had a favorable outcome. Fourteen patients (9%) had unfavorable outcomes: 4 deaths, 7 treatment changes, 2 bacteriological failures, and 1 withdrawal. During treatment, 85 patients (52%) developed myelosuppression, 69 (42%) reported peripheral neuropathy, and none had QTc(F) prolongation >500 ms. At 48 weeks of follow-up, 131 patients showed sustained treatment success with the resolution of adverse events in the majority. Conclusions: After 24–36 weeks of treatment, this regimen resulted in a satisfactory favorable outcome in pulmonary MDR-TB patients with additional drug resistance. Cardiotoxicity was minimal, and myelosuppression, while common, was detected early and treated successfully. Clinical Trials Registration: ClinicalTrials Registry of India (CTRI/2019/01/017310). Abstract : Highly drug-resistant pulmonary tuberculosis can be successfully treated with an entirely oral, short-course regimen of bedaquiline, delamanid, linezolid, and clofazimine. Toxicities can be identified early and corrected, thus reducing the duration, pill, and financial burden to the patient and program.